A Gavel to Ground: Examining the Effectiveness and Efficacy of Project Karunungan in Enhancing Local Governance and Its Future Direction - Danlag, Joanna Grace A.; Calva, Joy C. (PT FORMOSA CENDEKIA GLOBAL, 2024)
In the context of local governance, careful implementation of parliamentary procedures during meetings is of great concern. In 2019, Project Karunungan, a training workshop program, was born from cooperation between the Political Science Department of Mindanao State University and the Local Government Unit of General Santos City, Philippines. The initiative's primary goal is to educate barangay officials about Robert's Rules of Order principles. This paper is qualitative and quantitative research, drawing arguments from interviews and surveys. The correct parliamentary process significantly improves local governance by providing a formal framework for decision-making and guaranteeing fairness, openness, and accountability. This paper advances the significance of Project Karunungan to new heights as a continuous program to produce better leaders.